2007
DOI: 10.1089/end.2006.0350
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Holmium Laser and Pneumatic Lithotripsy in Managing Upper-Ureteral Stones

Abstract: In our study, the fragmentation rates of holmium laser-assisted ureteroscopy were significantly better in the upper ureter. The complications and the need for auxiliary procedures were significantly less for holmium laser-assisted ureteroscopy when compared with pneumatic lithotripsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 14 publications
5
37
0
3
Order By: Relevance
“…In addition to the studies showing 139 Akdeniz et al A comparison of efficacies of holmium YAG laser, and pneumatic lithotripsy in the endoscopic treatment of ureteral stones similarities between both groups [8][9][10] , some of them reported that LL is more effective with lesser complication rates. [11][12][13] In our study, successive cases who had undergone intracoporeal lithotripsy in the endoscopic management of ureteral stones have been retrospectively analyzed, Groups of PL, and LL have been compared.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the studies showing 139 Akdeniz et al A comparison of efficacies of holmium YAG laser, and pneumatic lithotripsy in the endoscopic treatment of ureteral stones similarities between both groups [8][9][10] , some of them reported that LL is more effective with lesser complication rates. [11][12][13] In our study, successive cases who had undergone intracoporeal lithotripsy in the endoscopic management of ureteral stones have been retrospectively analyzed, Groups of PL, and LL have been compared.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in medical technology increased the success rate of ureteroscopic lithotripsy. Laser lithotripsy has better stone-free rates and lower complications rates than pneumatic lithotripsy for upper-ureteral stones [4]. Furthermore, laser lithotripsy has advantages over pneumatic lithotripsy with low-retrograde migration of ureteral calculi [5] and flexible ureterorenoscopy (FURS) could reach the migrated stones in the same season.…”
Section: Introductionmentioning
confidence: 99%
“…Her iki yöntemi benzer olarak bildiren çalışmaların yanında (1-3), LL'nin daha etkin ve daha az komplikasyona sebep olduğunu bildiren karşılaştırmalı yayınlar mevcuttur (4)(5)(6). Bunun yanında LL'nin impakte taşlarda, üst üreter taşlarında ve pediatrik vakalarda PL'den daha etkin olduğunu bildiren yayınlar da mevcuttur (7)(8)(9).…”
Section: Introductionunclassified